2021
DOI: 10.1111/acer.14635
|View full text |Cite
|
Sign up to set email alerts
|

Antagonism of Sigma‐1 receptor blocks heavy alcohol drinking and associated hyperalgesia in male mice

Abstract: Background: Alcohol use disorder (AUD) is a complex psychiatric disease characterized by high alcohol intake as well as hyperkatifeia and hyperalgesia during withdrawal. A role for Sigma-1 receptors (Sig-1Rs) in the rewarding and reinforcing effects of alcohol has started to emerge in recent years, as rat studies have indicated that Sig-1R hyperactivity may result in excessive alcohol drinking. Sig-1R studies in mice are very scarce, and its potential role in alcohol-induced hyperalgesia is also unknown. Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 86 publications
3
12
1
Order By: Relevance
“…The findings are not easily compared between studies using different routes of administration and time of testing in withdrawal. Overall, the data presented here agree with literature showing three days as the optimal withdrawal time for induction hyperalgesia in mice following chronic alcohol drinking in a twobottle choice model [128,129]. Under the current experimental conditions of 72-hour withdrawal from alcohol, the effects on mechanical sensitivity and anxiety-like behaviors appear dissociable.…”
Section: Discussionsupporting
confidence: 89%
“…The findings are not easily compared between studies using different routes of administration and time of testing in withdrawal. Overall, the data presented here agree with literature showing three days as the optimal withdrawal time for induction hyperalgesia in mice following chronic alcohol drinking in a twobottle choice model [128,129]. Under the current experimental conditions of 72-hour withdrawal from alcohol, the effects on mechanical sensitivity and anxiety-like behaviors appear dissociable.…”
Section: Discussionsupporting
confidence: 89%
“…Notably, there were no group effects of EtOH drinking on pain sensitivity or affective behavior. While previous studies have seen effects of EtOH on pain sensitivity and affect (Quadir et al, 2021b) (Gong et al, 2017;Overstreet et al, 2005;Van Skike et al, 2015;Xu et al, 2021), others studies have not (Bloch et al, 2020;McNamara and Ito, 2021;Pirino et al, 2022) One potential explanation is that rats in the present study only drank for 3-4 weeks before behavioral testing and thus did not consume enough EtOH to produce behavioral deficits. Studies in Wistar rats report escalated intake after ~20 EtOH drinking sessions (Carnicella et al, 2009;George et al, 2012;Kimbrough et al, 2017); rats in this study only drank for 16 sessions.…”
Section: Discussionmentioning
confidence: 59%
“…These findings are in accordance with a previous study reporting that EtOH withdrawal increases nociceptive threshold(Schunck et al, 2015). However, it is important to note that many other studies have demonstrated EtOH-induced decreases in pain threshold (Avegno et al, 2018; Kang et al, 2019; Kononoff et al, 2018; Quadir et al, 2020a; Quadir et al, 2021a; Quadir et al, 2021b; Walcott et al, 2018; You et al, 2020). Our findings suggest male CRF1:cre: td Tomato rats may be resistant to the analgesic properties of EtOH; however, further studies will test thermal sensitivity during intoxication to directly address this speculation.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations